The Growth of Hexagonal Boron Nitride Quantum Dots on Polycrystalline Nickel Films by Plasma-Assisted Molecular Beam Epitaxy - Nurzal Nurzal; Wei-Cyuan Huang; Cheng-Yu Liu; Su-Hua Chen; Ing-Song Yu (Crystals, 2022)
In this report, quantum dots of hexagonal boron nitride (h-BN) were fabricated on the surface of polycrystalline Ni film at low growth temperatures (700, 750, and 800 °C) by plasma-assisted molecular beam epitaxy. Reflection high-energy electron diffraction could trace the surface condition during the growth and perform the formation of BN. The observation of surface morphology by scanning electron microscopy and atomic force microscopy showed the nanodots of BN on Ni films. The existence of crystal h-BN quantum dots was determined by the analysis of Raman spectra and Kevin probe force microscopy. The cathodoluminescence of h-BN quantum dots performed at the wavelength of 546 and 610 nm, attributed to the trapping centers involving impurities and vacancies. Moreover, the influence of temperatures for the substrate and boron source cell was also investigated in the report. When the k-cell temperature of boron and growth temperature of substrate increased, the emission intensity of cathodoluminescence spectra increased, indicating the better growth parameters for h-BN quantum dots.